2008
DOI: 10.1124/jpet.107.135798
|View full text |Cite
|
Sign up to set email alerts
|

The Protein Kinase A Pathway Contributes to Hg2+-Induced Alterations in Phosphorylation and Subcellular Distribution of Occludin Associated with Increased Tight Junction Permeability of Salivary Epithelial Cell Monolayers

Abstract: Hg2ϩ is commonly used as an inhibitor of many aquaporins during measurements of transcellular water transport. To investigate whether it could also act on the paracellular water transport pathway, we asked whether addition of Hg 2ϩ affected transport of radiolabeled probes through tight junctions of a salivary epithelial cell monolayer. Inclusion of 1 mM Hg 2ϩ decreased transepithelial electrical resistance by 8-fold and augmented mannitol and raffinose flux by 13-fold, which translated into an estimated 44% i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 39 publications
3
26
0
Order By: Relevance
“…In SMG-C6 cells, the initial TER value was 516.2698.62 V . cm 2 , which was consistent with previous reports in the same cell line (Kawedia et al, 2008) and represented a relatively 'tight' epithelium according to the description of electrical characteristics (Anderson and Van Itallie, 2009). 1 mmol/l capsaicin did not induce any change to TER values within 60 min (Fig.…”
Section: Activation Of Trpv1 Decreases Ter and Increases Paracellularsupporting
confidence: 81%
See 1 more Smart Citation
“…In SMG-C6 cells, the initial TER value was 516.2698.62 V . cm 2 , which was consistent with previous reports in the same cell line (Kawedia et al, 2008) and represented a relatively 'tight' epithelium according to the description of electrical characteristics (Anderson and Van Itallie, 2009). 1 mmol/l capsaicin did not induce any change to TER values within 60 min (Fig.…”
Section: Activation Of Trpv1 Decreases Ter and Increases Paracellularsupporting
confidence: 81%
“…2A, lower panels). Moreover, we extracted the cytoplasm and membrane protein fractions as previously described (Kawedia et al, 2008). Capsaicin induced a significant increase in occludin protein in the cytoplasm fraction within 60 min, together with a decrease in the membrane fraction.…”
Section: Activation Of Trpv1 Induces Redistribution Of Occludinmentioning
confidence: 99%
“…Contrasting studies, however, again highlight the potential multiplicity of occludin pSer and pThr sites and related cell-specific signaling effectors that mediate the functional diversity of this protein. In this respect, elevated pSer/pThr occludin levels have been correlated to increased epithelial permeability (58,88,130) as well as to BBB dysfunction in encephalitic mouse and human brain (127). Collins et al (26) also showed a reduction in pSer/pThr occludin levels in BAECs in response to physiological cyclic strain (i.e., a barrier-strengthening influence).…”
Section: Proteolytic Degradation (I) Mmp-dependent Proteolysismentioning
confidence: 99%
“…Several studies have demonstrated that PKA activity is important for the regulation and localization of TJ-associated proteins. Indeed, subcellular localization of claudin 1, paracellin-1 or occludin is dependent on phosphorylation by PKA in both physiological and pathological states (French et al, 2009;Ikari et al, 2006;Kawedia et al, 2008). Interestingly, Klingler et al (2000) showed that disruption of TJ barriers after calcium depletion could be preserved when PKA inhibitors were used.…”
Section: Discussionmentioning
confidence: 96%